Antenna Decoupling by Common and Differential Modes Cancellation - Sun, Libin; Li, Yue; Zhang, Zhijun; Wang, Hanyang (IEEE transactions on antennas and propagation, 2021)
In this article, a general decoupling method based on a new perspective of common mode (CM) and differential mode (DM) cancellation is proposed. For two closely spaced antennas, the mutual coupling effect can be analyzed and solved by exciting them simultaneously with in-phase (CM) and out-of-phase (DM) signals. It is theoretically proved that, if CM and DM impedances are the same, the mutual coupling effect between two separated antennas can be totally eliminated. Therefore, we can solve the coupling problem by CM and DM impedance analysis and exploit the unique field properties of characteristic modes to assist in antenna decoupling in a physical intuitive way. To validate the feasibility of this method, two practical design examples, including the decoupling between closely spaced dipole antennas and planar inverted-F antennas, are proposed. Both design examples have demonstrated that the proposed method can provide a systemic design guideline for antenna decoupling and achieve better decoupling performance compared to the conventional decoupling techniques. We forecast the proposed decoupling scheme, with a simplified decoupling procedure, has great potential for the applications of antenna arrays and multi-input multi-output (MIMO) systems.